Monster cats. 1 - Pandania (Seven Seas Entertainment, 2024)
"Is it a banshee, a yeti, a gorgon, or...a cat? Monster Cats are a purrfect new breed of familiar furry friends crossed with freaky fun! If you think life with regular cats can get complicated, wait till you see what it's like for people who live with these charming supernatural pets."--Back cover.